Blocking VCAM-1 Prevents Angiotensin II-Induced Hypertension and Vascular Remodeling in Mice - Yin, Liangqingqing; Bai, Jie; Yu, Wei-Jia; Liu, Ying; Li, Hui-Hua; Lin, Qiu-Yue (Frontiers in Pharmacology, 2022)
Adhesion of monocytes to the vascular endothelium frequently leads to an inflammatory response, which contributes to hypertension and vascular remodeling. Vascular cellular adhesion molecule-1 (VCAM-1) plays an important role in leukocyte adhesion and migration during inflammatory diseases. However, its role in angiotensin (Ang) II -induced hypertension and vascular dysfunction remains largely unknown. Wild-type (WT) mice were administered a VCAM-1 neutralizing antibody (0.1 or 0.2 mg/mouse/day) or IgG control and then infused with Ang II (490 ng·kg-1·min-1) or saline continuously for 14 days. Systolic blood pressure (SBP) was measured with a tail-cuff system, pathological changes in the aorta were assessed by histological staining, and vascular relaxation was analyzed an aortic ring assay. Our results indicated that compared with saline infusion, Ang II infusion significantly upregulated VCAM-1 expression in the mouse aorta and serum. Moreover, Ang II infusion markedly increased arterial hypertension, wall thickness, fibrosis, infiltration of Mac-2+ macrophages, reactive oxygen species (ROS) production and vascular relaxation dysfunction. Conversely, blockade of VCAM-1 with a neutralizing antibody substantially alleviated these effects. In vitro experiments further confirmed that the VCAM-1 neutralizing antibody inhibited Ang II-induced macrophage adhesion and migration and DNA damage and oxidative stress in endothelial cells (ECs). In conclusion, these results indicate that blockade of VCAM-1 exerts a protective effect against Ang II-induced arterial hypertension and dysfunction by regulating monocytes adhesion and infiltration into the endothelium and represents a novel therapeutic approach for hypertension.